(untitled) (LICERE - Revista do Programa de Pós-graduação Interdisciplinar em Estudos do Lazer, 2009)
The study intended, through phenomenological research, specifically the “situated phenomenon” method, to understand the educative processes present in the social practices of leisure, based on the speeches of three managers of two enterprise’s recreation clubs. In the data analyses the next categories were constructed: A) Leisure to relax and to return to work; B) Interpersonal relationship in leisure experiences; C) Leisure experiences provided by the enterprise. Being so, we could identify educative processes of cooperation, attention to rules, claim of rights, dialoguing, alienation and possibility of knowledge of a new place. These educative processes happen in the everyday interactions, through interpersonal relationships during leisure experiences provided by the enterprises.